UDC:616.36-005:75-642 TUBERCULOSIS AND ITS COURSE IN PATIENTS WITH HEPATITIS B - Masharipovа Sh.S; Masharipov S; Matyakubova D.Sh (Scientific Impulse, 2023)
In this study, the problem of hepatitis «В» in patients with drug resistant tuberculosis of the lungs is currently of great practical importance. The incidence of hepatitis «В» and tuberculosis continues to increase, and the epidemiological danger of this age group remains high. The factor that determines the peculiar course of the process is a decrease in the functional activity of the immune system.